The Impact of Service Quality, Customer Satisfaction and Loyalty Programs on Customer’s Loyalty: An Evidence from Telecommunication Sector - Sabir, Raja Irfan; Irfan, Muhammad; Sarwar, Muhammad Arslan; Sarwar, Binesh; Akhtar, Naeem (Journal of Asian Business Strategy, 2013)
All well reputed organizations know that the key to success lies in their customers. Hence in today’s world, the companies who do not provide value to their customers bring an opportunity for the competitors to jump in and steal these customers. Same rule applies in Telecommunication sector hence this research focuses on finding the impact of service quality, customer satisfaction and loyalty programs on customer’s loyalty in Telecommunication sector of Pakistan. All Telecom service provider companies ; U fone, Warid, Telenor, Zong, Mobilink and PTCL are taken in this research and purpose is to investigate the impact of service quality, customer satisfaction and loyalty programs on customer loyalty of these telecom service providers companies. A structured questionnaire was designed and survey was conducted to collect the data from 150 customers from different occupations in areas of Jhang and Okara districts of Punjab having different mobile phone connections of companies operating in Pakistan. A comparative analysis of companies is also made that shows that companies should focus on improving the quality of their services for better and greater customer satisfaction and customer loyalty.